Pembrolizumab in the management of metastatic melanoma. (November 2015) - Spain, Lavinia; Younger, Eugenie; Hatipoglu, Emine; Larkin, James
Pembrolizumab is a humanized IgG4 anti-PD-1 antibody that plays a major role in the treatment of advanced melanoma. Through blockade of PD-1, it leads to an increase in effector T-cell activity in the tumor microenvironment. Clinical trial outcomes for pembrolizumab in addition to pharmacokinetics, pharmacodynamics and safety of the compound are discussed in this article. Phase I trials have demonstrated safety and efficacy of pembrolizumab in advanced, pretreated melanoma patients. When compared with chemotherapy in a Phase II trial of ipilimumab-refractory patients, those treated with pembrolizumab showed superior progression-free survival. In addition, in the pivotal Phase III trial pembrolizumab improved overall survival compared with ipilimumab in patients naive to immune checkpoint inhibition. Pembrolizumab is well tolerated and has a favorable safety profile. Common adverse events are fatigue, rash, itching and diarrhea. Less frequent immune-related adverse events include hypothyroidism, colitis, hepatitis and pneumonitis.